The Relationship between Internet Usage and Gross National Income of an Emerging Economy - Chong, Fennee; Liew, Venus Khim-Sen; Rosita, Suhaimi (WSEAS, 2016)
This study examines both the long-run and short-run relationships between the internet usage rate and the gross national income per capita of an emerging economy – Malaysia. Empirical findings from the econometrics analysis of a thirteen years time series found that there is a significant long-run and short-run relationship between these two variables. Therefore, enhancing internet usage among the public and private sectors is a relevant strategy towards achieving a higher national income status for the people in this country.